KAJIAN HISTORIS KUMPULAN PUISI TIRANI DAN BENTENG KARYA TAUFIQ ISMAIL - Martalena, Martalena (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
The purpose of this research aim to know the representation of historical event and historical fact in Tirani dan Benteng poem anthology by Taufiq Ismail. The background of the study was the researcher’s interest on poems by Taufiq Ismail which were anthology in Tirani and Benteng. The poems told about the historical events at the end of Soekarno era. This study used historical approach. The method used in this study was content analysis. The scope of the study was the analysis toward of the historical event representations and historical facts representation in the anthology. The focuses of this study were: (a) historical event representations, (b) artifact representations, (c) sociofact representation, and (d) mentifact representation. The results show that: (1) the event historical reprentations were: G30S/PKI event, collapse of Indonesian economic joint, event demonstration student in Tritura action causing to die Arief Rachman Hakim, (2) the artifact representations were: jacket covered with blod, rumpled banner, flag at half mast, weapon and steel bayonet, (3) sociofact representations were poverty and vertical as well as horizontal class conflicts, (4) mentifact representations were the spirit to defend truth and justice and the aspiration of the youths involved in Tritura action.